2002
DOI: 10.1016/s0735-1097(01)01701-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of direct stenting with conventional stent implantation in selected patients with acute myocardial infarction

Abstract: In selected patients with AMI, direct stenting can be applied safely and effectively. This strategy may result in a significant reduction of microvascular injury, as suggested by improved ST-segment resolution after reperfusion with major potential clinical consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
1
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(122 citation statements)
references
References 32 publications
7
110
1
4
Order By: Relevance
“…In the postconditioned group, within 1 minute of reflow after the direct stenting, the angioplasty balloon was positioned just upstream of the implanted stent (so that it would not be damaged and to prevent possible thrombi embolization during in-stent balloon reinflation) and reinflated 4 times for 1 minute with low-pressure (4 to 6 atm) inflations, each separated by 1 minute of reflow (Figure 1). 16 This sequence of 4 brief episodes of ischemia-reperfusion was chosen arbitrarily because we recently demonstrated that a similar regimen triggers postconditioning in the rabbit heart. 17 When the balloon was positioned just upstream of the implanted stent in the postconditioned group, care was taken not to encompass a coronary branch.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…In the postconditioned group, within 1 minute of reflow after the direct stenting, the angioplasty balloon was positioned just upstream of the implanted stent (so that it would not be damaged and to prevent possible thrombi embolization during in-stent balloon reinflation) and reinflated 4 times for 1 minute with low-pressure (4 to 6 atm) inflations, each separated by 1 minute of reflow (Figure 1). 16 This sequence of 4 brief episodes of ischemia-reperfusion was chosen arbitrarily because we recently demonstrated that a similar regimen triggers postconditioning in the rabbit heart. 17 When the balloon was positioned just upstream of the implanted stent in the postconditioned group, care was taken not to encompass a coronary branch.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Direct stenting without predilation may decrease embolization and the incidence of the no-reflow phenomenon. 2,3 More specific approaches to the problem of microvessel embolization during PCI include thrombectomy by different techniques and the use of anti-embolic protection devices. One randomized trial has reported rheolytic thrombectomy to be effective in decreasing embolization in patients who underwent PCI on venous grafts or native coronary vessel with massive thrombosis 4 ; however, few data exist on the effectiveness of rheolytic thrombectomy in the setting of AMI.…”
mentioning
confidence: 99%
“…Direct stenting without predilatation also was more frequent after thrombus aspiration, which may have contributed to the favorable results. 107 Infarct size was not measured in this study. Thus, these results require confirmation in a multicenter randomized trial (with infarct size determination) before they can be considered definitive.…”
Section: Stone Interventional Strategies In Stemi 559mentioning
confidence: 88%